Preimplantation genetic risk reduction: a new dilemma in the era of chromosomal microarrays and exome sequencing. Issue 5 (November 2015) - Altarescu, Gheona; Beeri, Rachel; Lazer-Derbeko, Galit; Eldar-Geva, Talia; Steinberg, Avraham; Levy-Lahad, Ephrat; Renbaum, Paul
Abstract: New technologies are revealing genetic variants of unknown significance (VUS), raising questions about the indications that call for preimplanation genetic diagnosis (PGD). Two couples requesting PGD for VUS are presented. The first couple requested PGD for Lynch syndrome. Whole exome sequencing identified in a healthy male with a family history of Lynch-associated tumours, a MLH1 missense variant. The variant had not been reported as pathogenic, but was predicted as damaging by algorithms. The second couple had a child diagnosed with pervasive developmental disorder and intellectual disability, carrying a microduplication on chr:Xp.22.3, and a microdeletion on chr:17q21.31. The maternally inherited X linked microduplication was also present in the mother's healthy brother and daughter, whereas the chr17 microdeletion was a de-novo event. As chromosomal microarrays and whole-exome sequencing are becoming standard tests, couples are requesting PGD for these VUS. The risk of possible genetic diseases can be reduced by carrying out PGD for uncertain findings, yet will inevitably lead to the birth of affected children despite the transfer of embryos that are not carriers of the familial variants. Findings of unknown significance demand urgent discussion and guidelines for their use as a risk-reduction measure in the preimplantation setting.